Gender Performance Differences in High School Economics and Accounting: Some Evidence from New Zealand - Keef, S.P (School of Management Working Papers, 1990)
This paper sought to determine whether performances in the University Bursaries examinations exhibited any form of gender bias. in economics and accounting A multivariate analysis of variance, with repeated measures, was used to determine gender performance differentials after controlling for the effects of academic ability, concurrent study of mathematics courses and inter-year variability. Although some minor gender biases were observed, the results were generally in accord with the thesis that significant gender biases were absent. In contrast, the popularity of this course combination exhibited a strong gender bias. There were twice as many males as females.